ANALISIS PERBEDAAN RESPON SIKAP AUDIENCE ATAS STRATEGI PROMOSI PRODUCT PLACEMENT DALAM FILM HABIBIE & AINUN - Dastiana, Cynthia Dastiana; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2013)
The research was motivated by the phenomenon of the development of promotionalstrategies in product placement in movies, which aims to analyze whether there is any difference in audience response toward product placement promotion strategies in Habibie & Ainun Movie with many different backgrounds.The sample used in this study is the population living in the area of Semarang City and the age category, who have already watched Habibie & Ainun Movie, 17-20 years old, 21-24 yearsold, and above 25 years old. The sampling method which used in this study is quota sampling and the method for collecting data is questionnaire that distributed to 90 respondents. Processing of thedata is using descriptive analysis, the reliability test, validity, and one way ANOVA.The results of the analysis and discussion in this study state that, (1) there is no difference in audience response between male and female respondents, (2) there is differences in audienceresponse on the attention factors with the age category 17-20 years to 21-24 years, (3) there is no difference in audience response among respondents who chose one of the group of movie viewersfrequency, (4) there is no difference in audience response among respondents who chose one of the types of the most popular movie genres to be watched